Early Medieval Hillforts in the Territory of the Middle Volga Region - Airat M. Gubaidullin (Археология евразийских степей, 2022)
In the early Middle Ages, new archaeological cultures arose in the territory of the Middle Volga region. They influenced the formation of the ancestors of future peoples who now inhabit this region. An important place in their study belongs to fortified settlements, which were characteristic of that time period. They are an indicator of the development of any people of antiquity, as they reflect, in particular, the level of engineering, building skills of the population who left them, and other aspects. The study of the systems and structures of the Finnish hillforts in the Middle Volga indicates that the development of methods for building fortifications among the settled population of the region mostly took place on a local basis. These were mostly promontory forts, which were defended from the side of the field by 1–3 lines of ramparts and moats. They were simple earth embankments with no reinforcing inner structures. Hillforts were mainly located along the banks of large rivers and their tributaries. It is possible that in addition to close access to water resources and fishing, this was dictated by the needs of cultural and economic relations with the neighbors. The fortified settlements presented in the paper, belonging to various cultures that existed in the early Middle Ages, allow to trace the formation of the future engineering and related skills in construction among the population of the Middle Volga region in historical perspective.